2008
DOI: 10.1007/s11764-008-0061-2
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing physical well-being and overall quality of life among underserved Latina-American cervical cancer survivors: feasibility study

Abstract: An ethnically sensitive, behaviorally based telephone counseling approach with Latina Americans cervical cancer survivors can achieve short term improvements in physical well-being and overall QOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(66 citation statements)
references
References 64 publications
(116 reference statements)
1
56
0
2
Order By: Relevance
“…Three studies focused on the re‐entry phase alone while one focused on watchful waiting for prostate cancer and another on long‐term survivorship . Only one screened on the basis of psychosocial need, showing positive intervention effects .…”
Section: Resultsmentioning
confidence: 97%
“…Three studies focused on the re‐entry phase alone while one focused on watchful waiting for prostate cancer and another on long‐term survivorship . Only one screened on the basis of psychosocial need, showing positive intervention effects .…”
Section: Resultsmentioning
confidence: 97%
“…The cancer site-specific QOL instruments were developed to measure the QOL of cervical cancer patients. This category consisted of 3 scales: the EORTC Quality of Life Questionnaire-Cervix-24items (QLQ-Cx24) [33], the Functional Assessment of Cancer Therapy-Cervix (FACT-Cx) [34,35], and the Quality of Life Instruments for Cancer Patients-Cervical Cancer (QLICP-CE) [36]. The survivor-specific category included the Cancer Survivors' Unmet Needs (CaSUN) scale [37], which was developed to assess QOL among long-term cancer survivors using a needs-based approach.…”
Section: Resultsmentioning
confidence: 99%
“…Latino oncology patients, particularly Latinas, are less likely than nonminority patients to access and receive culturally and linguistically appropriate formalized psychosocial services, which complicates the identification of their psychosocial needs (Ashing-Giwa, 2008; Galvan, Buki, & Garces, 2009; Napoles-Springer et al, 2009). Moreover, research has shown that culture and ethnic factors influence how an individual understands, explains, and responds to the facts and meaning surrounding life-threatening diseases such as cancer; how side effects will be understood and experienced; how emotions will be expressed; and which treatments will be sought (Kawaga-Singer, 1995).…”
Section: Latino Culture’s Influence On Psycho-oncological Needsmentioning
confidence: 99%